(untitled) (Revista Innova Educación, 2022)
The objective of the research was to establish the relationship between academic procrastination, age and grade in high school students. A quantitative design of correlational type was used. A total of 148 students participated through a non-probabilistic intentional sampling. After informed consent, the Academic Procrastination Scale (EPA) was applied, which evaluates the levels of academic procrastination taking into account two dimensions: procrastination of activities and academic self-regulation. The results were analyzed through descriptive statistics and Spearman’s correlation coefficient was used in the SPSS 21 program. It is mainly concluded that academic procrastination was related to age and that there is no relationship between academic procrastination and course.